The Influence Of Organizational Culture On Generation Z Job Satisfaction At BRI Branch Letjen Sutoyo Malang - Prasetya, Ryan Alvarizky (Proceeding Economy of Asia International Conference, 2026)
Introduction/Main Objectives: This study examines how organizational culture influences the job satisfaction of Generation Z employees at BRI Branch Letjen Sutoyo Malang, a demographic group that increasingly dominates the workforce and values open communication, supportive environments, and meaningful work. Background Problems: Generation Z often experiences a mismatch between their expectations and the banking sector’s disciplined, hierarchical culture; therefore, this study asks: How does organizational culture shape Gen Z job satisfaction within BRI’s work environment? Research Methods: Data were collected through in-depth interviews and observations with three Generation Z employees who have worked for at least one year. The data were analyzed through thematic reduction, categorization, and triangulation to ensure validity. Finding/Results: The findings show that disciplined work culture, supportive leaders and seniors, effective onboarding, and positive peer relationships significantly enhance job satisfaction. Praise from customers and clear career prospects further strengthen Gen Z’s motivation and commitment. Conclusion: A supportive and well-structured organizational culture increases job satisfaction and encourages long-term retention among Generation Z employees. Strengthening onboarding, mentoring, and two-way communication is essential for sustaining a positive employee experience in the banking sector.